Epoxy primer coating filled microcrystalline cellulose treated with silane coupling agent on metal substrate / Mohd Hafizie Abd Kudus … [et al.] - Abd Kudus, Mohd Hafizie; Baharudin, Adzrie; Onn, Munirah; Musa, Luqman; Abd Aziz, Azniwati; Din, Siti Nor; Ahmad, Zuliahani (Universiti Teknologi MARA Shah Alam, 2023)
Epoxy resin was incorporated with microcrystalline cellulose (MCC) for the production of the primer coating. Various sonication times were applied for the purpose of determining the ideal sonication period that provides the best barrier performance. The coatings were also added with various 3-Aminopropyltriethoxysilane (APTES) loadings in order to improve the mechanical and corrosion resistance properties. Fourier Transform Infrared (FTIR) Spectroscopy analysis was carried out to examine the chemical interactions and diffusion between MCC, APTES, and epoxy resin. After nine days of immersion in a 5 % sodium chloride (NaCl) solution, the ideal sonication period was found to be 30 minutes, with no corrosion occurring aggressively and no flaking or blistering appears on the coating. The anticorrosive qualities of the primer coating were eventually enhanced by the addition of MCC modified with APTES. The addition of APTES had improved the interaction between MCC and epoxy, hence achieving better compatibility and promoting a uniformly dispersed MCC throughout the epoxy resin matrix. The Tafel polarization results found that the addition of APTES up to 9 % gave the lowest corrosion rate at 0.004 mm/year and the highest polarization resistances at 198.69 kꭥ. This is explained by the fact that enough MCC-APTES can serve as a physical barrier and obstruct the paths used by corrosive agent to diffuse. Therefore, the MCC-Epoxy treated APTES coupling agent for metal corrosion protection has thus been successfully created.